Diversidade genética em estoques de Jundiá da Amazônia (Leirarius marmoratus) - Mantovani, Laís Santana Celestino (2018)
The Brazilian fishery on the rise reveals the need to insert native species in intensive cultivation, demanding efficient technological packages. Parties that make the genetic improvement of the species, a stage that is necessary for studies of genetic variability to be effective. One of the objectives may be a future improvement program for the Amazonian Jundiá (Leiarius marmoratus). With rapid growth and rusticity, in addition to good organoleptic characteristics in its meat, it becomes a remarkable fish for cultivation. For reproductive success and quality of production, it is necessary to monitor the genetic variability of commercial stocks in order to capture losses from inbred or related mating. This work had as objective the genetic variability of three stages of Jundiá of the Amazon of the region of Campo Verde - MT. A total of 143 animals from Philadelphia (FI), Nova Mutum (NM) and Júina (JU) were evaluated. Using the DNA extraction protocol with NaCl and the PCR technique allied to micro-satellite flies, a difference between the stocks was obtained, where the highest value is found between the stocks FI x JU (Fst=0.049). The genetic distance analysis of Nei is also present among the three stocks, with the highest index among the stocks FI x NM (0.014). Factorial matching (AFC) and Bayesian rates indicated that the first three stocks are much more genetically, agreeing with the high Fis values and the low Ho levels. The results are comparable with the inventories in question, with low variability and with the addition of new genetic data in the establishment, with the objective of increasing the production capacity of genotypes for high inbreeding